Avaliação agronômica e nutricional de três híbridos de sorgo [Sorghum bicolor (L.) Moench] e de suas silagens em três estádios de maturação - Fernanda Samarini Machado (2009)
The aim of this work was to study the agronomic characteristics, chemical composition and the in vitro digestibility of the plants and their fractions (leaves, steam and panicle), and the quality parameters of the silages of the hybrids BRS 610, BR 700 and BRS 655 harvested at three maturation stages of the grains: milk, soft dough and floury. And from the analyses of this data, establish a comparison between the three hybrids and determine the ideal moment of ensilage for each one. The stand varied from 73 to 105 thousand plants per hectare and the BRS 655 presented lower stand than the others hybrids at the first and third cuts. The BR 700 had the smallest size at all maturations stages, and the BRS 610 and BRS 655 had the same height. There was dilution of the participation of the steam by the increasing percentage of panicle with the advance of maturity of the plant and the correlation (p<0.05) among these variables was 0,94. The BR 700 presented minor percentage of steam than the other hybrids at all cuts and major percentage of panicle at soft dough and floury stages. The production of green matter (GMP) was affected by the maturation stages, with variation from 31.10 to 68.71 t GM ha-1. The Dry Matter and Digestible Dry Matter productions varied from 11.65 to 17.70 t ha-1 and from 6.52 to 9.84 t ha-1, respectively, and didn’t change among maturation stages, for the hybrids BR 700 and BRS 655, but decreased in the third cut for the BRS 610. The dry matter contents of the plants varied from 25.73% to 43.96% and increased with maturity. The percentage of dry matter of the steams were higher for BR 700 and did not change among maturation stages. The panicles showed increasing values of dry matter with the advanced of maturity, while for the leaves the growth of dry matter was different among hybrids. The percentage of crude protein (CP) of the plant remained constant among cuts for all the hybrids and varied from 5.21% to 6.26%. The levels of CP of the parts of the plant varied differently among hybrids with the advancement of age. The values of neutral detergent fiber, acid detergent fiber, cellulose and lignin of the plants were not affected by maturation stages. The in vitro dry matter digestibility of the plants of BRS 610 didn’t change with the maturity, but decreased between milk and floury stages for BR 700 and BRS 655. The fibrous fractions and the values of the in vitro dry matter digestibility of the parts of the plants behaved differently among hybrids and harvest periods. All the silages were classified as excellent fermentation quality according to the fermentative parameters (DM, pH, ammoniac nitrogen and organic acids). Dry matter value was influenced by maturation stage and varied from 22.86% to 41.27%. The contents of NDF, ADF and cellulose of the silages were lower in the floury stage in relation to milk, but the values of hemiceluloses and lignin didn’t change between harvest periods. The digestibility of the silages varied from 50.73% to 55.55% and behaved differently with the maturity for each hybrid. In the milk stage the BRS 610 showed the minor value of digestibility, while in floury stage it was better than the others.